L’avènement de la science météorologique du XVII$^{\protect e}$ au XIX$^{\protect e}$ siècle - Beaudouin, Denis (Comptes Rendus. Mécanique)
Since ancient times, natural phenomena have been observed and described, the first stage in the development of knowledge, often involving supposedly supernatural forces. It was in Europe in the 17th century that a scientific approach was developed, which became meteorology in the 19th century. A scientific approach required instruments, and it was in Florence in 1608 that the first thermometer was manufactured. Fifty years later, Ismaël Boulliau, the first French scientist to receive a thermometer from Florence, followed an approach based on observation and recording. This article sets out to show how, over the course of two centuries, a truly scientific meteorology emerged at the dawn of the twentieth century.